RESPONSE OF DIFFERENT TYPE OF FERTILIZERS ON GROWTH OF TWO GROUNDNUT (Arachis hypogaea L.) VARIETIES IN KATSINA A SUDAN SAVANNAH - Ibrahim, A. M. (FUDMA JOURNAL OF SCIENCES, 2022)
The experimental trial was conducted to evaluate the response of different types of fertilizers on the growth of two groundnut varieties in Katsina a Sudan savannah. The experiment was conducted during the 2020 and 2021 rainy seasons at Samaru farm Mani LGA, Katsina State, Nigeria. Treatments consisted of two varieties of groundnut (SAMNUT 25 and SAMNUT 26) and four different types of fertilizer (zero fertilizer, organic manure, NPK 30:30:30 and poultry manure) replicated three times. The treatments were factorized and laid out in a randomized complete block design (RCBD).  The result shows that groundnut growth components such as: the number of leaves per plant, leaf area index and days to 50% flowering per plot was significantly influenced by different types of fertilizer and SAMNUT 25 (Pâ‰¤0.05) outperformed SAMNUT 26. Different types of fertilizer Applications also recorded a significant (Pâ‰¤0.05) effect on growth parameters. However, the Application of poultry manure significantly (Pâ‰¤0.05) outperformed better on the number of leaves and leaf area index at 3, 6 and 9 WAS but during the 2020 growing season at 6 WAS organic manure recorded the highest (105) number of leaves. The study revealed that the application of poultry manure on SAMNUT 25 proves to promote better growth of groundnut in the study area.
Keywords: Groundnut Varieties, growth component, NPK fertilizer, organic manure, poultry manure